Performance Evaluation of DCT And Wavelet Coding of Image Transmission By Using of DM Technique Over Topical Shallow-Water Environment - Nilasari, Sendi Eka; Puja Astawa, I Gede; Santoso, Tri Budi (Politeknik Elektronika Negeri Surabaya (PENS), 2013)
Image transmission over under water acoustic channel is one of research trends that were developed to support under ocean environment monitoring. The result of study about the source coding performance for image transmission over underwater acoustic channel over tropical shallow-water environment is presented in this paper. By using the discrete cosine transform (DCT) and wavelet coding, image file was compressed and converted into binary data sequence. Transmission process was conducted with multicarrier OFDM system over under water acoustic channel. An evaluation has been implemented on base band scale by adopting channel model of previous research. With the DCT technique at Eb/No 20 dB was achieved the value of PNSR 12.69 dB, and bit error 0.0025. While by using the wavelet technique, at same Eb/No value, achieved the value of PSNR at 21.38 dB and bit error rate 0.0022. The performance evaluation also conducted visually and showing similar trend as simulation result by using pseudo random data.Keywords: DCT, wavelet, OFDM, underwater acoustic.